Childhood constipation is not associated with characteristic fingerprint patterns. Issue 12 (11th December 2003) - Jackson, C R; Anderson, B; Jaffray, B
Abstract : Background: It has been suggested that there is an association between simple arch fingerprint patterns and severe childhood constipation. If real, this association might be useful to predict which children have a poor prognosis. Aim: To see how many severely constipated children have simple arches, compared to non-constipated controls and their first degree relatives. Methods: Fingerprints were classified by two blinded assessors in 30 children requiring surgery for refractory constipation, and 30 children with appendicitis, and the first degree relatives of both groups. Colonic transit times and clinical outcomes were also evaluated among constipated children. Results: At least one simple arch was found in similar numbers of constipated children (13%) and their families (16%), and control children (7%) and their families (13%). Arch positivity was commoner among relatives of arch positive (6/6) than arch negative children (14/54), regardless of bowel history. Arch positivity did not identify children with prolonged transit times, nor those who required colectomy. Conclusions: Fingerprint patterns are not associated with severe childhood constipation, do not aid their management, and do not support a genetic aetiology for this problem.